Trends in ischemic stroke outcomes in a rural population in the United States - Chaudhary, Durgesh; Khan, Ayesha; Shahjouei, Shima; Gupta, Mudit; Lambert, Clare; Avula, Venkatesh; Schirmer, Clemens M.; Holland, Neil; Griessenauer, Christoph J.; Azarpazhooh, M. Reza; Li, Jiang; Abedi, Vida; et al. (Journal of the neurological sciences, 2021)
The stroke mortality rate has gradually declined due to improved interventions and controlled risk factors. We investigated the associated factors and trends in recurrence and all-cause mortality in ischemic stroke patients from a rural population in the United States between 2004 and 2018. This was a retrospective cohort study based on electronic health records (EHR) data. A comprehensive stroke database called “Geisinger NeuroScience Ischemic Stroke (GNSIS)” was built for this study. Clinical data were extracted from multiple sources, including EHR and quality data. The cohort included in the study comprised of 8561 consecutive ischemic stroke patients (mean age: 70.1 ± 13.9 years, men: 51.6%, 95.1% Caucasian). Hypertension was the most prevalent risk factor (75.2%). The one-year recurrence and all-cause mortality rates were 6.3% and 16.1%, respectively. Although the one-year stroke recurrence increased during the study period, the one-year stroke mortality rate decreased significantly. Age > 65 years, atrial fibrillation or flutter, heart failure, and prior ischemic stroke were independently associated with one-year all-cause mortality in stratified Cox proportional hazards model. In the Cause-specific hazard model, diabetes, chronic kidney disease and age < 65 years were found to be associated with one-year ischemic stroke recurrence. Although all-cause mortality after stroke has decreased, stroke recurrence has significantly increased in stroke patients from rural population between 2004 and 2018. Older age, atrial fibrillation or flutter, heart failure, and prior ischemic stroke were independently associated with one-year all-cause mortality while diabetes, chronic kidney disease and age less than 65 years were predictors of ischemic stroke recurrence. •Study cohort comprised of 8561 ischemic stroke patients from a rural population.•One-year all-cause mortality decreased between 2004 and 2018.•One-year stroke recurrence increased between 2004 and 2018.•Significant rise in stroke risk factors like hypertension, diabetes, dyslipidemia.